DJ-1 contributes to adipogenesis and obesity-induced inflammation - Kim, Jung-Min (Nature Publishing Group, 2014)
Adipose tissue functions as an endocrine organ, and the development of systemic inflammation in adipose tissue is closely associated with metabolic diseases, such as obesity and insulin resistance. Accordingly, the fine regulation of the inflammatory response caused by obesity has therapeutic potential for the treatment of metabolic syndrome. In this study, we analyzed the role of DJ-1 (PARK7) in adipogenesis and inflammation related to obesity in vitro and in vivo. Many intracellular functions of DJ-1, including oxidative stress regulation, are known. However, the possibility of DJ-1 involvement in metabolic disease is largely unknown. Our results suggest that DJ-1 deficiency results in reduced adipogenesis and the down-regulation of pro-inflammatory cytokines in vitro. Furthermore, DJ-1-deficient mice show a low-level inflammatory response in the high-fat diet-induced obesity model. These results indicate previously unknown functions of DJ-1 in metabolism and therefore suggest that precise regulation of DJ-1 in adipose tissue might have a therapeutic advantage for metabolic disease treatment.